Investigating diagenesis of archaeological bones from Etton Causewayed Enclosure, UK - Loy, Charlotte; Brock, Fiona; Dyer, Chris (Elsevier, 2023)
Diagenesis of archaeological bones proceeds via a complex combination of chemical, physical and/or microbial processes often over several millennia. These processes are influenced by the depositional environment, including fluctuations in pH, mineral availability and water table. This study investigates diagenetic alterations to the mineral and organic (collagen) phases of bones from a Neolithic site, Etton Causewayed Enclosure (Cambridgeshire, UK). Archaeological bones from some layers of the gravel site at Etton exhibit unusual staining patterns, including iron and manganese rich layers underneath the exterior bone surface and manganese speckling throughout the bone. A range of analytical techniques (micro-CT, FTIR, XRF and SEM-EDS) were employed to investigate the mineralisation within three bones from this site. Diagenesis appears to have occurred through a combination of bacterial degradation and mineral formation due to the changing redox conditions at the site caused by fluctuating groundwater. The reason for the positioning of the manganese layers beneath the iron layers at the surfaces of the bone remains unclear.
Keywords: Bone diagenesis; Manganese; Iron; Taphonomy; Redox conditions